The Color Violaceous, or, Chemistry and the Romance of Dematerialization: The Subliming of Iodine and Shelley's "Adonais" - Peterfreund, Stuart (Studies in romanticism, 2003)
Peterfreund discusses the abiding interest of Percy Bysshe Shelley in the chemical researches of Humphry Davy. One readily apparent reason for Shelley's interest in Davy's work has to do with what the former must have seen as an intellectual and metaphysical affinity with the latter, with respect to understanding how causation operates in the world. While, Davy's chemical researches were subject, as all such researches are, to the several laws of conservation, his research on iodine furnished Shelley with an imaginative construct to figure, if not to test, the possibilities of transcendence.